The Representation of Edith Stein in Contemporary German Historical Culture - Bernhardt, Markus (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The article deals with the representation of Edith Stein in contemporary German historical culture. Being complex, Edith Stein’s biography is demanding to describe. Finding a narrative, which would embrace her whole live in a comprehensible way, is therefore a formidable task. The analysis of her representation in German historical culture has revealed that different groups in the German society use certain images of Stein for their own purpose. They choose a convenient part of her life that best supports the purposes of their specific project, be it a school, clinic, church, et cetera. Thus Edith Stein becomes a quarry in which everybody can find what they need to find.